Comparison of Data Security and User Privacy on Instagram and Twitter: A Literature Study - Dwi Santoso, Arly Maya Berlyanti; Eva Alisya Febrianti; Fitri Mutia (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This comprehensive literature study examines and compares data security and user privacy features on social media platforms such as Instagram and Twitter. The method used is a literature study of 25 journal articles from various trusted sources, such as Scopus, ScienceDirect, and Web of Science, with a qualitative approach. The study reveals that Instagram has advantages in some aspects of data security and privacy compared to Twitter. However, both platforms have weaknesses that users should be aware of, including the risk of phishing and cyberattacks. The research also highlights the importance of individual awareness and the implementation of effective data security measures, such as two-factor authentication and strict privacy settings. Although the study provides valuable insights, there are limitations in data collection methods that rely on electronic sources, which may not cover all relevant literature. Therefore, future research is expected to overcome these limitations and provide more up-to-date recommendations for improving data security and user privacy on social media.